Estonia : Selected Issues. (IMF Staff Country Reports; Country Report, 1996)
This Selected Issues paper assesses the economic recovery in Estonia that began in 1994 and accelerated in 1995, highlighting the extent to which the pattern of production has changed since the beginning of the transition in 1992, the factors that made the decline in output inevitable early on, and the sound policies that made an early recovery possible. The paper lists the policy requisites to maintain, and indeed strengthen, the growth momentum. The paper also analyzes Estonia's experience with declining but persisting inflation since the introduction of the currency board in 1992.